Etiological spectrum for dysphonia in a rural Indian treatment seeking population - Mathew, Amrita Suzanne; Sridhar, Aishwarya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Aim of the study was to identify and analyse the etiological factors for dysphonia in a rural treatment seeking population in South India. Methods: 100 consenting patients presenting to the Department of Otorhinolaryngology in our rural hospital with change in voice for more than 4 weeks and undergoing detailed clinical evaluation including videolaryngoscopic examination and other relevant investigations to arrive at a definitive diagnosis, were included in a cross sectional descriptive clinical study. Descriptive and inferential statistical analysis was performed. Results: Organic/structural and functional dysphonia constituted 87% and 13% of cases respectively. The commonest causes for dysphonia were laryngopharyngeal reflux disease (LPRD) (35%), laryngeal/hypopharyngeal malignancies (16%) and vocal palsy/paresis (12%). The mean age of the study patients was 38.71±5.82 years. Majority (65%) were aged 21–50 years. Vocal palsy was identified in children aged 1–10 years (1%), and muscle tension dysphonia in those aged 11–20 years (2%). In individuals aged 21–50 years, LPRD (28%), functional dysphonia (9%), vocal nodules (8%) and vocal palsy (7%) were the most common causes. Laryngeal/hypopharyngeal malignancy (14%) was the commonest etiology identified in individuals aged ≥51 years. Male:female ratio was 1.1:1. The most frequently observed cause for dysphonia was laryngeal/hypopharyngeal malignancy (15%) in males, and LPRD (22%) in females. Conclusions: With its vast etiology, dysphonia is often just the “tip of the iceberg” for a much greater underlying disease process. This study serves as an insight into the possible differential diagnosis based on age, gender and geographic location of patients. As observed, the most common causes for dysphonia are LPRD and laryngeal/hypopharyngeal malignancies; both of which are amenable to prevention by lifestyle modification, early detection by appropriate clinical and investigative measures, and suitable treatment. Early and correct identification of the cause for dysphonia, enables early management, thereby reducing its associated morbidity and mortality.